Pharmacokinetic Interaction between TAK-044, a New Endothelin Antagonist, and Ciclosporin in Rats - Maeshiba, Yoshihiro; Yamashita, Kenji; Tsukuda, Ryoichi; Yoshimura, Yoshinobu (Arzneimittelforschung, 2002)
The pharmacokinetic interaction between TAK-044 (cyclo[D-α-aspartyl-3-[(4-phenylpiperazin-1-yl)carbonyl]-L-alanyl-L-α-aspartyl-D-2-(2-thienyl) glycyl-L-leucyl-D-tryptophyl] disodium, CAS 157380-72-8) and ciclosporin (CAS 59865-13-3) was investigated after concomitant intravenous (i.v.) administration in rats. After i.v. administration of 14C-labeled TAK-044 ([14C]TAK-044 alone at a dose of 3 mg/kg, the radioactivity concentration in the plasma was 1.65 µg/ml at 5 min and decreased biphasically with half-lives of 0.09 h and 0.39 h. AUC0–1h was 0.38 µg · h/ml. The pharmacokinetics of [14C]TAK-044 were affected dose-dependently by coadministration with ciclosporin. The AUC value for [14C]TAK-044 was increased 5-and 14-fold by the coadministration with cyclosporin at doses of 3 and 10 mg/kg, respectively. On the other hand, TAK-044 (3 and 10 mg/kg) did not change the pharmacokinetic parameters for ciclosporin (3 mg/kg). Biliary excretion is the major elimination route for both TAK-044 and cyclosporin. Ciclosporin delayed biliary excretion of [14C]TAK-044 in a dose-dependent manner, which might be due to inhibition of process(es) of hepato-biliary excretion of TAK-044. In conclusion, the AUC values for TAK-044 in rats are increased dose-dependently by coadministration with ciclosporin. Therefore, it may be necessary to adjust the dosage of the TAK-044 in combination with ciclosporin in the course of the first clinical trials.
Keywords: CAS 59865-13-3; CAS 157380-72-8; Ciclosporin; Cyclo[D-α-aspartyl-3-[(4-phenylpiperazin-1-yl)carbonyl]-L-alanyl-L-α-aspartyl-D-2-(2-thienyl); glycyl-L-leucyl-D-tryptophyl] disodium; Endothelin antagonist; TAK-044, pharmacokinetic interaction, rat